2006
DOI: 10.1007/11755494_26
|View full text |Cite
|
Sign up to set email alerts
|

Persuasive GERONtechnology: An Introduction

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Studies following this approach have been extraordinarily helpful to improve understanding of and mitigate individual lag. They proceed on the assumption that users have to use the technology in question 31 and thus have to live up to its demands. As such, they downplay a user's potential desire and ability to selectively and innovatively engage with technological environments.…”
Section: Empirical Researchmentioning
confidence: 99%
“…Studies following this approach have been extraordinarily helpful to improve understanding of and mitigate individual lag. They proceed on the assumption that users have to use the technology in question 31 and thus have to live up to its demands. As such, they downplay a user's potential desire and ability to selectively and innovatively engage with technological environments.…”
Section: Empirical Researchmentioning
confidence: 99%
“…A possible explanation for this phenomena could be observed in Schulz et al [25], which investigates the differences between the sequential and simultaneous approach of behaviour change. The study found out that there were higher dropout rates in a simultaneous conditions group compared toa sequential one hence suggesting that targeting one behaviour at a time (physical activity only as the main component of the intervention) was more effective in encouraging behavioural change [27].…”
Section: Discussionmentioning
confidence: 96%